The handbook of financial modeling : a practical approach to creating and implementing valuation projection models - Avon, Jack (Apress, 2021)
Financial modeling is a crucial concept for business leaders to understand and execute effectively, but few have the tools necessary to do so. While many professionals are familiar with financial statements and accounting reports, not many are truly proficient at building an accurate and practical financial model from the ground up. The Handbook of Financial Modeling provides these skills and so much more. Now in its second edition, The Handbook of Financial Modeling takes into account the new tech released since its successful initial release. Author Jack Avon uses his expertise to analyze the changes and improvements in industry-wide financial modeling through the past five years, in addition to instilling core concepts for readers of all experience levels. Approaching your company's financial issues with a modeler's perspective will transform and improve the rest of your business career's trajectory. Financial professionals, students, business leaders, aspiring CFOs, and more will come away with all the tools necessary to precisely and efficiently monitor an organization's assets and project future performance. The engaging case studies and Avon's expert analysis leave you prepared to monitor and predict your organization's finances effectively. Financial modeling's latest technology is at your fingertips, and this book's deep understanding of the topic ensures that you stay ahead of the pack.
Keywords: Finance -- Mathematical models.; Economics.; Finance.; elektronické knihy; electronic books